RNA extractions of mangosteen (Garcinia mangostana L.) pericarps for sequencing - Azhani Abdul-Rahman,; Najah Izzati Suleman,; Wan Adibah Zakaria,; Goh, Hoe-Han; Normah Mohd Noor,; Wan Mohd Aizat, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study employed several RNA extraction methods for mangosteen pericarps prior to RNA sequencing. The sequencing platform heavily relies on a high quality RNA yield. However, pericarp tissues contain a lot of phenolic compounds that results in low RNA quality. Hence, we studied several RNA extraction methods to obtain the most suitable method for the best RNA quality from the pericarps of mangosteen. Five different methods including Lopez and Gomez, modified hexadecyltrimethyl ammonium bromide (CTAB) method, several commercial kits from TranszolUP, Favorgen and Qiagen RNeasy were compared. By optimising the CTAB method, it was found to be the best method to obtain pure RNA (high A260/A280 ratio) with the highest yields (up to approximately 600-800 ng/μL concentration). The QC control of these samples using bioanalyzer validated their suitability for the downstream RNA sequencing. This report details the method for extracting high quality and high yield RNA samples from fruit that are rich in polyphenolic compounds such as mangosteen.